PERILAKU PENJAJA PANGAN JAJANAN ANAK SEKOLAH TERKAIT GIZI DAN KEAMANAN PANGAN DI JAKARTA DAN SUKABUMI - Ghaida Yasmin; Siti Madanijah (Jurnal Gizi dan Pangan, 2010)
The purposes of this research were to identify and to analyze behaviour of school-food vendor related to nutrition and food safety in Jakarta and Sukabumi. This research used secondary data from Survey “National Monitoring and Verification Food Safety of Elementary Student Street-food 2008” by SEAFAST and BPOM RI. The subjects of this research are 79 school-food vendors in Jakarta and 29 school-food vendors in Sukabumi. Descriptive statistical method is used to process all the data. Most of the subjects were elementary school graduated (46.3%) and used handcart as tool for sale of street-foods (31.5%). Only 35.2% had attended a food safety education/training program. As the result of it, 48.1% of the subjects had sufficient nutrition and food safety knowledge. There were significant differentiation of nutrition and food safety knowledge between the subjects which had been classified by vendor group, level of education, and participation in food safety education/ training program. As many as 74.1% of the subjects lack of food safety practices. There were significant differentiation of food safety practices between the subjects which had been classified by vendor group, region, and level of education. Spearman’s correlative test shows that there a positive correlation between level of education with nutrition and food safety knowledge, level of education with food safety practices. Pearson correlative test shows that there was no significant correlation between nutrition and food safety knowledge with food safety practices.